EFFECT OF COUNSELING WITH KNOWLEDGE OF POPLE ABOUT DENUGE FEVER PREVENTION (STUDY IN TEJO VILLAGE SUB-VILLAGE MOJOAGUNG SUB-DISTRICT JOMBANG DISTRICT - Zuhroh, Ita Ni'matuz (Well Being, 2019)
Dengue Fever is a disease with high morbidity in Indonesia, in East Java reported cases of Dengue Fever in 2015 as many as 1,817 cases have been reported by the service of East Java Province. Because of many people that had got less information about this disease. So, this infection of dengue fever was so fast spreading. Purpose of this research is to know there is an effect of counseling with knowledge of the people about dengue fever. This method used the analytic step with pre-experiment design with “One Group Pre–Test, Post–Test Design” type. The population is all people in Ds. Tejo as many as 150. The sample was got from 40 respondents by processing data used editing, coding, scoring, tabulating, and cross-sectional approach. From the result of the research, it is shown that 37 respondents before getting counseling of information had less knowledge as many as 17 respondents (44%) and after getting counseling, they had enough information as many as18 respondents (50,0%). Based on Wilcoxon test result that significance level as many as 0,001is less than 0,05 (ρ= 0,001 < α = 0,05) so that it can be concluded that H1 is accepted. There is an effect between counseling with knowledge of people to dengue prevention.